The Meaning of Sacred Space on the Architecture of the Historic Mosque Case Study of Masjid Jami 'Al Mukarromah Kampung Bandan North Jakarta - Ashadi Ashadi; Anisa Anisa; Finta Lissimia (International Journal of Built Environment and Scientific Research, 2018)
The building of worship is a building that has sacred spaces as a container of its activities. The case study taken in this research is the historic mosque which is often referred to as a sacred mosque because of the tomb of Habib Islamic syiar carrier. The existence of the tomb inside the mosque is what makes the mosque visited by pilgrims and pilgrims and has various activities related to worship and pilgrimage. The purpose of this research is to get a conclusion about the sacred space and its meaning in Masjid Jami 'AlMukarromah Kampung Bandan. This research uses descriptive interpretive method. Field observations were conducted by, first, observation of study subjects, ie by observing the activities undertaken at Masjid Jami 'Al Mukarromah Kampung Bandan. From activity observation can be found sacred activity and profane activity. Second, observing the spaces used sacred activities that are done in the mosque. Interviews were conducted with the main sources and direct descendants of Habib Alwi bin Ali As-Syatiri. The result of this study is that the sacred space of the Jami 'AlMukarromah mosque has a clear definition and is reflected in its physical form. The sacred space used is the main prayer room as the sacred space which has the highest hierarchy. The main prayer room is part of the expansion building. Sacred space of pilgrimage is on the part adjacent to the tomb and the original part of the mosque which is often called the Nine pillars. The area adjacent to the tomb is an important area so the expansion or renovation of the mosque does not change the original form. The sacred space used for the haul activity is the same as the sacred space for pilgrimage, that is, in the section adjacent to the tomb and pillar of nine